Ventilatory and cardiovascular responses of a python (Python molurus) to exercise and digestion - Secor, S M; Hicks, J W; Bennett, A F (Journal of experimental biology, 2000)
To investigate the potential limiting steps of peak metabolic rates, we examined gas exchange rates ( vdot (O2), vdot (CO2)), respiratory exchange ratio (RER), breathing frequency, tidal volume, minute ventilation volume (V.e) as well as the heart rate, systemic blood flow and stroke volume of Burmese pythons (Python molurus) while fasting at rest, exercising, digesting and exercising while digesting. All measured variables increased significantly during exercise (crawling at 0.4 km h(-)(1) and at vdot (O2max)), highlighted by a 17-fold increase in vdot (CO2) and a 24-fold increase in V.e. During the digestion of a meal equivalent to 25 % of the snake's body mass, pythons responded with increases in vdot (O2) and heart rate similar to those experienced during exercise, along with a 4.5-fold increase in systemic blood flow. Interestingly, pythons hyperventilated while exercising, whereas they hypoventilated during digestion. The combined demands of exercise and digestion resulted in significantly higher vdot (O2), vdot (CO2), breathing frequency and heart rate than during either exercise or digestion alone. Evidently, the capacities of the ventilatory and cardiovascular systems to transport oxygen to locomotor muscles are not a limiting factor in the attainment of peak metabolic rates during exercise in pythons